(untitled) (Research, Society and Development, 2020)
Introduction: The literature has shown vitamin D deficiency in obese individuals, which contributes to the manifestation of low-grade chronic inflammation. Therefore, this review aims to provide updated information on the relationship of vitamin D with the inflammatory process triggered in obesity. Methodology: A bibliographic survey was performed in the Pubmed, SciELO, LILACS and Cochrane databases, using the following keywords: "vitamin D" and "inflammation"; "obesity" and "inflammation"; "vitamin D", " obesity” and“ inflammation ”. Results and Discussion: Obese individuals appear to have vitamin D deficiency due to inadequate intake or increased uptake of this vitamin by adipose tissue which may contribute to the increase of chronic low grade inflammation present in obesity. Conclusion: The inadequate intake of vitamin D contributes to the manifestation of its deficiency in obese. However, further studies are needed, considering that the metabolism of this micronutrient is not completely elucidated.